THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS OF SMP TP 45 DENPASAR IN ACADEMIC YEAR 2021/2022 - Ni Komang Kadri; Ni Wayan Krismayani; I Ketut Wardana (Academic Journal on English Studies (AJOES), 2022)
The present study is an ex-post facto research with correlation design was intended to figure out the significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMP TP 45 Denpasar in the 2021/2022. The sample of this study was 40 students which were taken with a random sampling method. The matching cloze procedure test and the short answer test were used as research instruments. Based on computations by SPSS 20 version, score of coefficient correlation, which is obtained 0.615 and this score was compared with the r-table with degree of significant 5%, Therefore, the score of coefficient correlation was very high in comparison with the score of r-table, which means that the alternative hypothesis was accepted. It was found that there was a significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMP TP 45 Denpasar in academic year 2021/2022.